MODEL PENGEMBANGAN PERANGKAT PEMBELAJARAN SEJARAH BERORIENTASI METAKOGNITIF JENJANG SMA - Utomo, Cahyo Budi (History Department, Semarang State University and Historian Society of Indonesia, 2015)
The importance of metacognitive based history learning in the high school level as requested in the â€œcurriculum 2013â€ is the main background of this research. The research is focused to find the model of development of metacognitive based learning through research and development (R&D) type research. The results showed an essential component in achieving successful management of metacognitive based history learning in high school education which the curriculum as a core competency analysis and basic competencies, lesson plan development, and the development of assessment tools. Development model of metacognitive based learning at high school education have main characteristic of the inclusion of explicit metacognitive learning goals and assignments and devices equipped with a rubric and assessment questionnaire. Metacognitive based history learning instructional tools that are developed in senior high school level has been carried out as optimally as possible by involving history teachers in the process of development and testing through focus group discussions and questionnaire.Keywords: Model, Instructional tool, Metacognitive, senior high school levelPentingnya orientasi metakognitif dalam perangkat pembelajaran sejarah jenjang SMA sebagaimana yang dikehendaki dalam implementasi kurikulum 2013 merupakan latar belakang utama penelitian ini. Penelitian difokuskan untuk menemukan model pengembangan perangkat pembelajaran berorientasi metakognitif melalui penelitian berjenis riset dan pengembangan (R&D). Metode penelitian R&D dilaksanakan melalui tiga tahap utama yaitu: tahap studi pendahuluan, tahap pengembangan, dan tahap uji publik. Hasil penelitian menunjukkan komponen esensial dalam mewujudkan keberhasilan penge-lolaan pembelajaran sejarah berorientasi metakognitif pada jenjang pendidikan SMA adalah kurikulum sebagai bahan analisis kompetensi inti dan kompetensi dasar, pengembangan RPP, dan pengembangan perangkat assesmen. Model pengembangan perangkat pembelajaran sejarah berorientasi metakognitif pada jenjang pendi-dikan SMA yang dikembangkan memiliki ciri utama pada pencantuman tujuan pembelajaran metakognitif secara eksplisit dan dilengkapi dengan penugasan dan perangkat assesmen berupa rubrik dan angket. Pengembangan perangkat pembelajaran sejarah berorientasi metakognitif pada jenjang pendidikan SMA telah dilaksanakan seoptimal mungkin dengan melibatkan guru dalam proses pengembangan dan pengujian melalui FGD dan pengisian angket.Kata Kunci: Model, Perangkat Pembelajaran, Metakognitif, Jenjang SMAÂ Â